In situ synthesis of metal (Bi0)-semiconductor [BiOX (X = Cl, Br, and I)] nanocomposites as a highly effective catalyst for the reduction of 4-nitrophenol to 4-aminophenol - Singh, Dinesh; Poddar, Pankaj (New Journal of Chemistry, 2024)
The reduction of 4-nitrophenol (4-NP) to 4-aminophenol (4-AP) has been efficiently catalyzed by in situ generated Bi-0-BiOX (X = Cl, Br, I) nanocomposites in the presence of sodium borohydride (NaBH4). The hierarchical 3D arrays of precursors (BiOCl, BiOBr, and BiOI) have been synthesized by a facile co-precipitation method at ambient temperature. The metallic Bi-0 is generated in situ by partial reduction of the Bi3+ ions in BiOX (X = Cl, Br, and I) mediated by NaBH4 during the conversion of 4-NP to 4-AP. In situ generated Bi-0-BiOX shows better catalytic activity than Bi-0-BiOX composite formed by mixing individually synthesized metallic Bi-0 particles with semiconducting BiOX nanoparticles. The Bi-0-BiOI nanocomposite demonstrated higher catalytic activity (k(app) = 0.529 min(-1)) compared to Bi-0-BiOCl (k(app) = 0.095 min(-1)) and Bi-0-BiOBr (k(app) = 0.098 min(-1)) due to its efficient conversion into metallic Bi-0. The approximate percentage composition of in situ generated metallic Bi-0 on the surface of BiOCl, BiOBr, and BiOI is nearly 10, 17, and 25%, respectively. Further, the reduction of 4-NP has been completed within 24, 22, and 6 minutes by in situ generated Bi-0-BiOCl, Bi-0-BiOBr, and Bi-0-BiOI nanocomposites from BiOCl, BiOBr, and BiOI, respectively. Extensive studies have been conducted to generate a better understanding of the actual catalytic sites present on the surface of the catalysts.